1998
DOI: 10.1002/(sici)1099-0488(199812)36:17<3087::aid-polb9>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Relaxational mode structure for optical probe diffusion in high molecular weight hydroxypropylcellulose

Abstract: We studied translational diffusion of dilute monodisperse spheres (diameters 14 < d < 455 nm) in aqueous 1 MDa hydroxypropylcellulose (0 ≤ c ≤ 7 g/L) at 25°C using quasielastic light scattering. Spectra are highly bimodal. The two spectral modes (“slow,” “fast”) have different physical properties. Probe behavior differs between small (d < Rh) and large (d ≥ Rg) probes; Rh and Rg are the matrix polymer hydrodynamic radius and the radius of gyration, respectively. We examined the dependences of spectral lineshap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 18 publications
4
26
0
Order By: Relevance
“…The stretched exponential form used in the line shape analysis provides an accurate while not necessarily unique representation for the field correlation function. To understand the physical properties of the scatterers one can carefully study the behavior of A i , θ i , and β i for each mode as function of scattering angle and temperature as was previously reported for HPC polymer chains20–23 However, the unattractive feature of this approach is that θ i , the pseudorate of relaxation, has the dimensions of time to a noninteger power β i which is not the same in different spectra and different modes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stretched exponential form used in the line shape analysis provides an accurate while not necessarily unique representation for the field correlation function. To understand the physical properties of the scatterers one can carefully study the behavior of A i , θ i , and β i for each mode as function of scattering angle and temperature as was previously reported for HPC polymer chains20–23 However, the unattractive feature of this approach is that θ i , the pseudorate of relaxation, has the dimensions of time to a noninteger power β i which is not the same in different spectra and different modes.…”
Section: Discussionmentioning
confidence: 99%
“…HPC is readily available, FDA‐approved nontoxic food additive used in soups and ice creams as an emulsifier9 and encapsulator 10. Because of its electrical neutrality, semiflexible nature, and solubility in a wide range of solvents, HPC has been widely used for studies of polymer dynamics 11–24…”
Section: Introductionmentioning
confidence: 99%
“…However, experiments on multiple systems (26)(27)(28)(29) find that logðg ð1sÞ ðq; DÞÞ depends non-linearly on q 2 . The convention in most light scattering papers is that q is in units radians/cm, to be contrasted with the cycles/ m of the PGSE NMR q.…”
Section: Non-fickian Diffusion Is Normal In Fluidsmentioning
confidence: 99%
“…Optical‐probe methods were applied to HPC/water systems by Brown and Rymden,7 Yang and Jamieson,8 Russo and coworkers,9, 10 and Streletzky and Phillies 11, 12, 16–18. Brown and Rymden7 found that 720‐Å spheres diffuse through solutions of 800 kDa HPC more rapidly than expected from η p .…”
Section: Introductionmentioning
confidence: 99%
“…For 907‐Å‐radius probes, the slow‐mode relaxation rate corresponds to the Stokes–Einstein diffusion coefficient. Streletzky and Phillies11, 12, 16–18 studied probe diffusion in aqueous 1 MDa HPC with optical probes with radii of 70–2270 Å and at HPC concentrations ranging from dilute to nearly 4 c + . Their QELSS field correlation functions were bimodal: where subscripts s and b refer to the sharp and broad modes, A s and A b are mode amplitudes, θ s and θ b are relaxation pseudorates, and β s and β b are stretching exponents.…”
Section: Introductionmentioning
confidence: 99%